Perfil de voláteis, de aroma, de vitamina e, ácidos graxos em óleos extraídos de resíduos agroindustriais de uva (Vitis spp.) por prensagem a frio - Olegário, Lary Souza (2016)
In 2012 Brazil processed 830.915 tons of grapes. It is estimated that this activity generated 37.000 tons of waste‟s containing seeds. In Italy, France and Spain, the grape seeds are used for oil extraction; but in Brazil, this activity is little explored, although it aggregates profits to industry and reduce environmental pollution. The objective of this research was to evaluate the potential of wastes generated by grape industrialization in Brazil for the production of oil for culinary and cosmetic applications. Seeds from five grape wastes generated by agro industries located in the São Francisco Valley and the Semi-Arid Embrapa (PE/BA, Brazil) were dried, crushed and submitted to cold pressing under 45tons. The oils were characterized physically and chemically on their relative density, peroxide, acidity, saponification and iodine values, in addition to their fatty acid profiles and tocopherols and tocotrienols contents. The volatile compounds present in the headspace of the oils were identified comparatively to a commercial oil. The volatiles were isolated by SPME (DVB/Car/PDMS), separated by a HP-5MS capillary column and analyzed by GC-MS system. The isolation conditions were optimized by varying the adsorption temperature (40°C-70°C) and the extraction time (20- 45min) by DCCR, and determined by Response Surface Methodology and Desirability function. Trained judges using QDA, generated the five oils aroma profiles, comparatively to three commercial oils, and the results were analyzed by ANOVA, Tukey (p≤0.05) and PCA. The seeds showed lipid content between 12.3 and 22.8% (d.b); the cold pressing process yielded between 42 and 67%. Overall, the oils showed physicochemical parameters within the ranges established by the Codex Alimentarius Commission presenting relative densities close to 0.92g.cm-3 , peroxide values between 3.86 and 12.25meqO2.kg-1 , acidity between 0.08 and 0.12 mgKOH.g-1 , values of saponification between 192.00 and 193.00mgKOH.g-1 , and iodine between 131.24 and 137.25cgI2.g-1 . Their profiles of fatty acids were very similar among them, with linoleic (C18: 2) as the major fatty acid, ranging from 63.9 to 70.6%, followed by oleic and palmitic acids. The oils showed very different profiles of tocopherols and tocotrienols. Maximum values (mg/kg oil) were: 10.8 of α-tocopherol for the Chenin Blanc oil, and 16.1 of γ-tocopherol, 249.2 of α-tocotrienol and γ-tocotrienol of 249.8 for the Isabel oil. The optimized isolation of the volatiles occurred for the fiber exposure at 61.5ºC for 39minutes. In general, the esters were a major chemical class in oils, especially those generated from the vinification of the Syrah and Tempranillo grapes, in which this chemical class represented 59.5 and 77.2% of the total area of the samples chromatogram, respectively. These samples‟ esters contents justified their higher intensities (p≤0.05) of aromatic notes described as "sweet", "fruity", "floral", "banana" and "freshness". The great differences between the oils studied with respect to their sensory and volatile profiles, recommends a prestudy of the grape agro industrial residues, when they are intended for the extraction of oil for culinary or cosmetic applications, cases when the aroma defines the quality of the final product.